The critical issue linking lipids and inflammation: Clinical utility of stopping oxidative stress - Bale, Bradley Field; Doneen, Amy Lynn; Leimgruber, Pierre P.; Vigerust, David John (Frontiers in Cardiovascular Medicine, 2022)
The formation of an atheroma begins when lipoproteins become trapped in the intima. Entrapped lipoproteins become oxidized and activate the innate immune system. This immunity represents the primary association between lipids and inflammation. If the trapping continues, the link between lipids and inflammation becomes chronic and detrimental, resulting in atherosclerosis. If entrapment ceases, the association between lipids and inflammation is temporary and healthy, halting the atherosclerosis process. Therefore, the link between lipids and inflammation depends upon lipoprotein retention in the intima. The entrapment is due to electrostatic forces uniting apolipoprotein B to polysaccharide chains on intimal proteoglycans. The genetic transformation of contractile smooth muscle cells in the media into migratory secretory smooth muscle cells produces the intimal proteoglycans. The primary stimulus for this genetic change is the platelet-derived growth factor, which are produced by activated platelets. Oxidative stress is the main stimulus to activate platelets. Therefore, minimizing oxidative stress would significantly reduce the retention of lipoproteins. Less entrapment decreases the association between lipids and inflammation. More importantly, it would halt atherogenesis. This review will analyze oxidative stress as the critical link between lipids, inflammation, and the pathogenesis of atherosclerosis. Through that perspective, we will discuss stopping oxidative stress to disrupt a harmful association between lipids and inflammation. Numerous therapeutic options will be discussed to mitigate oxidative stress. This paper will add a new meaning to the morse code international distress signal SOS-‘stop oxidative stress’.